(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2021)
The industrial interest in phytoplanktonic microorganisms such as microalgae and cyanobacteria are due to the high biotechnological potential they have in synthesizing bioactive compounds, ease of adapting to different sources of nutrients, extreme survival conditions and the bioabsorbent capacity of heavy metals mainly in wastewater. The objective of this study was to isolate and characterize phenotypically and genotypically phytoplanktonic microorganisms from stabilization pools in Engabao, Guayas-Ecuador, using different culture media and molecular markers ITS, ITS2, LSU and 16S RNAr. The results of the cell culture during seven days showed the Chls1 microalgae with BG11 pH 7.8 medium reached 25.4 x 106 cells mL-1, the cyanobacterium Syn1 was 340.6 x 106 cells mL-1, while for Nod1 chlorophyll analysis was used to reach on the seventh day 6.33 μg mL-1. Molecular studies were carried out using a modified gDNA extraction and purification protocol, obtaining optimal DNA concentration and quality for the three strains: Chls1 146 ng µL-1, Syn1 326 ng µL-1 and Nod1 158.8 ng µL-1. The use of polyphasic analysis based on morphological characters and gDNA of the strains, was amplified by PCR and sequenced; the strains identified phenotypically and genotypically by the primers ITS2, ITS and LSU correspond to the microalgae Chlorella sorokiniana with 99.48%, 99.07% and 99.77% identity similarity, while the cyanobacterial isolates Synechococcus sp. and Nodosilinea sp. with the analysis of the 16S RNAr region, it presents identity percentages of 97.47% and 99.83%; despite not using specific primers for these microorganisms, the use of several regions increases the reliability of taxonomic and phylogenetic identification; these species have a high biotechnological potential and a great economic impact.